Development Of Building Information Modeling (Bim) Implementation Framework In Malaysian Construction Industry - Abdul Rahim, Nur Soleha (2020)
Building Information Modeling (BIM) is anticipated to be mandated starting 2019 onwards for public projects in Malaysia. However, the BIM implementation is still at a nascent stage. Therefore, there is urgency for the Government to monitor the trend of BIM development in the construction industry. This study aims to determine and evaluate the current phase of BIM development in the construction industry with the consideration of sustainability aspects and demand-supply based on two perspectives, namely contractors (demand) and academic institutions, focusing on final year students (supply). The findings from the questionnaire survey show that 72% of the contractors are still at the awareness phase of BIM development; whereas 22% at the adaptation phase, 3% at the adoption phase and 3% at the application phase. In addition, the results also indicate that 73% of the contractors perceive that there is no urgent demand on BIM skilled graduates. From the supply perspective, only 19% of the future graduates have 1 to 5 years of experience on BIM highlighting the needs for academic institutions to provide more BIM related-training (skills), facilities and networking in the future. Additionally, 68% of the contractors are only aware of BIM contribution towards environmental sustainability compared to economic (43%) and social (11%) sustainability. It is expected that this study can assist the government in monitoring the development of BIM in the construction industry as well as contributes to the literature and knowledge particularly in the civil engineering and construction management area.